Resiliens hinsides modstand og tilpasning:: En samtidsdiagnostisk genealogi over tre begreber - Hansen, Bue Rübner (Slagmark - Tidsskrift for idéhistorie, 2018)
Over the recent decades, the concept of resilience has spread from environmental science to a number of disciplines dealing with crisis and disaster management. From psychology, public health, and human resource management to development and security studies, resilience is replacing an earlier focus on resistance and adaptability within these fields. There exist several studies dealing with resilience discourse as a key to a diagnostic of the present. While some hail resilience as a new register of ecological resistance for social movements, other decries resilience as a discourse legitimating the neoliberal state’s abandonment of the poor to catastrophe. This article proposes a framework for reading together these highly diverging interpretations of resilience through a historicising of the concept of resilience, tracing its rise genealogically in relation to the concepts of resistance and adaptability. Through readings of authors such as Thomas Hobbes, Carl von Clausewitz, Herbert Spencer, and C.J. Holling, the article shows how these concepts were imported from scientific materialism into pragmatic and normative discourses of defence of life against shifting threats to individual and social life. The article shows how the shifting importance of the concepts of resistance, adaptability and resilience must be related to changing social-ecological problems and the forms of contestation and governance that respond to them.